A low-calorie rebaudioside D–glucose–sodium sweetener matches sucrose in palatability and neural responses in a functional MRI study of healthy adults - Nakamura, Yuko; Takahashi, Rika; Ohkuri, Tadahiro (Frontiers in Nutrition, 2026)
IntroductionNon-nutritive sweeteners (NNSs) often taste less palatable than glucose-containing sugars, potentially because they differentially engage sweet taste pathways. In this study, we examined a low-calorie rebaudioside D–glucose–sodium (RebD mix) sweetener, formulated on the basis of previous evidence that its components can engage type 1 taste receptors 2 and 3 (T1r2/T1r3) and sodium–glucose cotransporter 1 (SGLT1)–related pathways. We tested whether the RebD mix matches sucrose in palatability and neural responses.MethodsA within-subject fMRI study was performed on 28 healthy adults [mean age 22.36 ± standard deviation (SD) 5.20 years; male = 22: body mass index (BMI) kg/m2 = 20.34 ± 2.22 SD]. During scanning, participants received three gustatory conditions in randomized order, with tasteless rinses (9 s) between trials: sucrose (234 mM), RebD mix (29.2 mM sucrose + 194.3 mM glucose + 0.156 mM RebD + 5 mM sodium gluconate), and RebD mix without sodium (Na+) (29.2 mM sucrose + 194.3 mM glucose + 0.184 mM RebD), which is known to enhance SGLT1 activation. Liking and wanting ratings for gustatory stimuli were obtained at scanning. Imaging analyses focused on the orbitofrontal cortex (OFC), a key region associated with palatability, and OFC-centered functional connectivity, using within-participant contrasts across the three gustatory conditions.ResultsLiking and wanting did not differ across the three conditions. OFC response to the RebD mix did not differ from sucrose, whereas the RebD without Na+ condition showed greater OFC–postcentral gyrus connectivity than the other two conditions (psBonferroni–corrected < 0.001). Across participants, OFC–postcentral connectivity in the RebD without Na+ condition was negatively associated with fullness measured at scanning.ConclusionThe RebD mix matched sucrose in subjective palatability and OFC responses, while removal of Na+ altered OFC– postcentral gyrus connectivity linked to satiety. These findings indicate that the RebD mix, a novel low-calorie formulation, may achieve sucrose-comparable palatability.